The Food Safety and Inspection Service's Role in the Control of Listeria Monocytogenes - Drake, Timothy (My University, 2025)
I began my Applied Practical Experience (APE) in April 2025 with the Food Safety and Inspection Service (FSIS) with my preceptor Dr. Gregory Abreu, a Deputy District Manager at FSIS. Dr. Kastner, Dr. Abreu, and I videoconferenced to discuss the field experience and to consider ideas for my APE products. Dr. Abreu identified a need for presentation to FSIS supervisors about their role in food safety with a focus on the control of Listeria monocytogenes. I worked with Dr. Abreu to identify Agency policy to present, and I gave the presentation to the FSIS supervisors in September 2025. I interviewed Dr. Abreu for a career introspective article in the One Health Newsletter which helped me consider my future career options. He described his journey through veterinary school, work in a large animal practice, and service in public health with FSIS. Dr. Kastner suggested that I participate in the International Mobility of Veterinary Students & Food Biotechnologists (iMOVES&FB) trip to Italy as part of my APE to help round out my field experience by giving me food safety related insights from within the European Union. I learned about differences in Italian food safety and biosecurity compared to the United States (U.S.). The trip helped to give me a multidisciplinary view of food safety. I included my systems thinking tool in my ILE which describes how I applied thinking tools in my APE products.
Keywords: food safety and inspection service; FSIS; listeria monocytogenes; meat and poultry; listeriosis